Secukinumab for the treatment of adult‐onset pityriasis rubra pilaris: a single‐arm clinical trial with transcriptomic analysis. (1st November 2022) - Boudreaux, Blake W.; Pincelli, Thais P.; Bhullar, Puneet K.; Patel, Meera H.; Brumfiel, Caitlin M.; Li, Xing; Heckman, Michael G.; Pittelkow, Mark R.; Mangold, Aaron R.; Sluzevich, Jason C.
Abstract: Background: The pathogenesis of pityriasis rubra pilaris (PRP) is not completely understood, but interleukin (IL)‐17 has been shown to play a critical role. There are no reliable immunomodulatory agents to treat PRP. We conducted an open‐label, single‐arm clinical trial of secukinumab, a monoclonal antibody that inhibits IL‐17A, for the treatment of PRP. Objectives: To evaluate the clinical efficacy of secukinumab and define the transcriptomic landscape of PRP and its response to IL‐17A blockade. Methods: Twelve patients with PRP were recruited for an open‐label trial of secukinumab. Patients received a 24‐week course of secukinumab. The primary endpoint was a ≥ 75% reduction in Psoriasis Area and Severity Index (PASI 75) from baseline to week 28. Secondary endpoints included PASI 90, change in Physician's Global Assessment (PGA), and change in Dermatology Life Quality Index (DLQI). RNA sequencing was performed on lesional and nonlesional skin biopsies obtained at baseline and week 2. Sample groups were compared to identify differential gene expression and pathway enrichment. This trial was registered with ClinicalTrials.gov : 'Cosentyx (secukinumab) for the treatment of adult onset pityriasis rubra pilaris' – NCT03342573. Results: At week 28, six of 11 patients (55%) achieved PASI 75, and three patients (27%) achieved PASI 90. PGA (P = 0.008) and DLQI scores (P = 0.010) showed significant improvement with treatment. No serious treatment‐related adverse events were encountered. Treatment with secukinumab normalized transcriptional differences between lesional and nonlesional skin. Transcriptomic data from nonresponsive patients suggest that overactivity of innate immune pathways may be driving resistance to secukinumab. Conclusions: Secukinumab appears to be an effective treatment for PRP and warrants further investigation. PRP is a transcriptionally heterogeneous disease, reflecting its variable response to therapy. Agents targeting other IL‐17 isoforms and innate immune mediators should be considered for future clinical trials. What is already known about this topic?   The pathogenesis of pityriasis rubra pilaris is incompletely understood. Successful treatment has been reported with a variety of immunomodulatory agents, but disease is often refractory to therapy. Interleukin (IL)‐17 is thought to drive keratinocyte proliferation and vascular dysfunction in this disease. A previous trial demonstrated efficacy of the anti‐IL‐17A drug ixekizumab for pityriasis rubra pilaris. What does this study add?   Herein we describe the findings of a clinical trial of secukinumab, an anti‐IL‐17A monoclonal antibody, for the treatment of pityriasis rubra pilaris. Secukinumab was effective in treating pityriasis rubra pilaris. Our transcriptomic data give new insight into the expressional changes that occur in response to secukinumab and suggest mechanisms of treatment resistance. Abstract: Secukinumab was effective in treating pityriasis rubra pilaris. Improvement in lesional gene expression profiles correlated with disease response and preceded clinical improvement. Linked Comment:  D.M.W. Balak and R. Rissmann. Br J Dermatol 2022; 187:633–634 . Plain language summary available online